2022
DOI: 10.3390/catal12101170
|View full text |Cite
|
Sign up to set email alerts
|

Copper Supported on MgAlOx and ZnAlOx Porous Mixed-Oxides for Conversion of Bioethanol via Guerbet Coupling Reaction

Abstract: The direct conversion of biomass-derived ethanol to high-valued-added chemicals has attracted widespread attention recently due to the great economic and environmental advantages. In the present study, the conversion of bioethanol through the Guerbet coupling process was studied in a fixed-bed reactor for MgAlOx and ZnAlOx mixed-oxides supported Cu catalysts. From the results, Cu adding into the system greatly enhance the dehydrogenation of ethanol and increase the H-transfer in the course of Guerbet coupling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In Zone II (Figure 6) associated with the formation of ─CH3 and ─CH2 groups, a higher intensity (2900─2600 cm -1 region) is observed for the zeolite with a lower Si/Al ratio (i.e., Z26, Figure 6a) than for zeolites with a higher Si/Al ratio (Z280 and Z371 in Figures 5b and c, respectively) [48]. The above suggests that, in addition to facilitating ethanol adsorption, zeolite Z26 promotes the formation of C2H4, which is confirmed by the bands at ⁓2880 and ⁓1645 cm -1 [49]. However, desorption of ethoxy groups is slower in zeolite Z26…”
Section: Drifts Of Ethanol Dehydration On Different Zeolitesmentioning
confidence: 58%
See 2 more Smart Citations
“…In Zone II (Figure 6) associated with the formation of ─CH3 and ─CH2 groups, a higher intensity (2900─2600 cm -1 region) is observed for the zeolite with a lower Si/Al ratio (i.e., Z26, Figure 6a) than for zeolites with a higher Si/Al ratio (Z280 and Z371 in Figures 5b and c, respectively) [48]. The above suggests that, in addition to facilitating ethanol adsorption, zeolite Z26 promotes the formation of C2H4, which is confirmed by the bands at ⁓2880 and ⁓1645 cm -1 [49]. However, desorption of ethoxy groups is slower in zeolite Z26…”
Section: Drifts Of Ethanol Dehydration On Different Zeolitesmentioning
confidence: 58%
“…Furthermore, in Zone II it is observed that the dopant also influences the formation of ethoxy species involved in the formation of C2H4 [49]. Both dopants (i.e., Ce and Cu) show less intense bands in the 2900─2600 cm -1 region compared to the undoped samples (Figure 6), which would be associated with their lower selectivity to C2H4 (Figure 3).…”
Section: Drifts Of Ethanol Dehydration On Different Zeolitesmentioning
confidence: 98%
See 1 more Smart Citation
“…However, when the support of NiAlO x was replaced by ZnAlO x , the product distribution changed greatly, with a large amount of ethyl acetate (Sel. of 42%) appearing in the system [34]. Previously, Boscolo et al also found that the ethanol conversion, product selectivity and carbon deposition would be greatly affected by the support component, as the Mg 2+ ion was partially substituted by Fe 2+ , Co 2+ , Ni 2+ , Cu 2+ and Zn 2+ ions [21].…”
Section: Introductionmentioning
confidence: 94%
“…For the NiFeO x , the largest amount of weak acidic sites (131.6 µmol/g) is shown when compared with those of NiAlO x (42.0 µmol/g) and NiCoO x (37.3 µmol/g). This might decrease the selectivity of the Guerbet coupling process, as the acid sites are often reported to be beneficial for the dehydration reaction in producing ether and ethyl acetate [19,34].…”
Section: Catalytic Performance Of Different Catalysts In Ethanol Coup...mentioning
confidence: 99%